2017
DOI: 10.1038/s41598-017-11952-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Suppressor of Hairless impedes its DNA-binding activity

Abstract: Notch signalling activity governs cellular differentiation in higher metazoa, where Notch signals are transduced by the transcription factor CSL, called Suppressor of Hairless [Su(H)] in Drosophila. Su(H) operates as molecular switch on Notch target genes: within activator complexes, including intracellular Notch, or within repressor complexes, including the antagonist Hairless. Mass spectrometry identified phosphorylation on Serine 269 in Su(H), potentially serving as a point of cross-regulation by other sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…Su(H) S269D mutants were developmentally delayed and died before pupation, comparable to what was observed for the null allele Su(H) attP , and in agreement with a functional loss due to impaired DNA-binding (Figure 1B) (Nagel et al, 2017;Praxenthaler et al, 2017). By contrast, the phospho-deficient Su(H) S269A mutants were nearly indistinguishable from the Su(H) gwt wild type control with respect to developmental timing and hatching rate (Figure 1B).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Su(H) S269D mutants were developmentally delayed and died before pupation, comparable to what was observed for the null allele Su(H) attP , and in agreement with a functional loss due to impaired DNA-binding (Figure 1B) (Nagel et al, 2017;Praxenthaler et al, 2017). By contrast, the phospho-deficient Su(H) S269A mutants were nearly indistinguishable from the Su(H) gwt wild type control with respect to developmental timing and hatching rate (Figure 1B).…”
Section: Resultssupporting
confidence: 83%
“…Generation of Phospho-Site Specific Su(H) Mutants in the Endogenous Locus Previously, we showed that Su(H) is phosphorylated at Serine 269 in Drosophila S2 cells, and that the introduction of a negative charge at this position interfered with the DNAbinding capability and transcriptional activity of Su(H). In addition, tissue-specific overexpression studies suggested that both, activation and repression of Notch signaling activity might be regulated by the phosphorylation of Su(H) at this site (Nagel et al, 2017). Based on the dominant negative character of the overexpression phenotypes, we were unable to decide on the biological relevance of the phosphorylation in vivo.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors also hypothesize this phosphorylation to be plausible in humans. Similarly another site in the beta-trefoil domain (BTD), on S269 (corresponding to S195 in humans) was also discovered in Drosophila melanogaster and is shown to inhibit the binding of BTD to DNA [ 174 ].…”
Section: Ptms Of the Notch Transcriptional Complex (Csl And Maml)mentioning
confidence: 99%
“…Additionally, in Drosophila, Su(H) has been discovered to have a supplementary phosphorylation site on the Serine 269 residue. This residue is highly conserved and may influence interactions with the NICD or DNA (Nagel et al, 2017). Further examination in relation to RBPJ-k binding on the NRE sites within the SPS on Hes1 must be conducted;…”
Section: Notch Dimerizationmentioning
confidence: 99%